(untitled) (Perspectivas de las Ciencias Económicas y Jurídicas, 2024)
This work was prepared within the framework of the Affiliation in the "B" chair of Provincial and Municipal Public Law at the National University of Córdoba. During the course of this period, the depths of the study of federalism and the jurisdictional disputes between the different levels of government were penetrated. In this essay, the main discussions that revolve around the traffic law are overturned and, in particular, the municipal powers are analyzed when it comes to issuing the national driver’s license. In particular, the investigation focuses on the arguments set forth in the "Ananía" ruling of the Superior Court of Justice of the Province of La Pampa.